Pyogenic liver abscess mimicking pleural effusion - M. Abiodun; W. Osarogiagbon; O. Oviawe (South African Family Practice)
Pyogenic liver abscess is a major visceral abscess that may pose a diagnostic dilemma in a febrile child with prominent extra-abdominal symptoms. We present a case of a well-nourished, immunocompetent four-year-old girl who had none of the common predispositions to a liver abscess. Hence, in this unusual setting, pyogenic liver abscess was not considered at the initial assessment, until closer evaluation and futile efforts to drain a seemingly large “pleural effusion” eventually revealed the diagnosis, which was confirmed by imaging. She underwent ultrasound-guided percutaneous drainage of the pyogenic liver abscess to avert the sequelae of this potentially fatal disorder. This underscores the need to think laterally when considering differential diagnoses for the sick child.